Digital transformation of Egyptian marine fisheries: A pathway to sustainable fisheries management - EL-Sira, Ibrahim; Tilley, Alexander; Samy-Kamal, Mohamed; Walid, Elsawy Aly (Elsevier, 2025)
To effectively manage fisheries, timely data of fishing operations and landings are needed by various stakeholders to make decisions. Although many technologies exist for fisheries' monitoring, control, and surveillance (MCS), low- and middle-income countries are often under-resourced and lack the capacity to establish and maintain these systems. To guide the formation of an effective MCS system for Egypt’s Mediterranean fisheries, this study investigates the current challenges in the sector, reviews national, regional, and European Union fisheries legislation, and evaluates the successes and suitability of low-cost and scalable digital systems used elsewhere. Results highlight significant gaps in current practices, such as manual, paper-based logbooks for reporting, and tracking of fishing vessels. We describe the design of a proposed low-cost digital workflow integrating electronic reporting with tiered vessel tracking. Our approach builds on tested technologies and international best practices that enhance data accuracy and strengthen compliance with regional and international regulations. This integrated system offers a promising pathway towards improving data-driven decision-making, enhancing fisheries management, and ensuring the long-term sustainability of Egypt's Mediterranean fisheries. This approach not only ensures regulatory compliance and promotes sustainable fisheries management, but also improves traceability, thereby strengthening adherence to standards and expanding market access.